Notes on Coleophora (Lepidoptera: Coleophoridae) injurious to Lycium (Solanaceae), with descriptions of two new species from China - Li, Houhun (Zootaxa, 2006)
This paper treats three species of Coleophora injurious to Lycium barbarum Linnaeus (Solanaceae) in China. Coleophora ningxiana n. sp. and Coleophora neolycii n. sp. are described as new, and Coleophora mosasaurus (Falkovitsh) is reported for the first time from China. A checklist and key to Coleophora injurious to Lycium on a worldwide basis are provided. Descriptions and illustrations of the Chinese species are given.